Noise and vibration mitigation for rail transportation systems : proceedings of the 12th International Workshop on Railway Noise, 12-16 September 2016, Terrigal, Australia /: proceedings of the 12th International Workshop on Railway Noise, 12-16 September 2016, Terrigal, Australia. (2018) - Unknown
No abstract available